Metabolite elucidation of 2‐fluoro‐deschloroketamine (2F‐DCK) using molecular networking across three complementary in vitro and in vivo models. Issue 1 (20th September 2021) - Gicquel, Thomas; Pelletier, Romain; Richeval, Camille; Gish, Alexandr; Hakim, Florian; Ferron, Pierre‐Jean; Mesli, Vadim; Allorge, Delphine; Morel, Isabelle; Gaulier, Jean‐michel
Abstract: This work first aims to investigate metabolites of 2‐fluoro‐deschloroketamine (2F‐DCK), a new arylcyclohexylamine derivatives (a group of dissociative ketamine‐based substances) using two in vitro experimental approaches, and to compare obtained results by means of molecular networking. Metabolites of 2F‐DCK were investigated using both human liver microsomes (HLMs) and hepatic (HepaRG) cell line incubates using molecular networking approach: 2F‐DCK pure substance was incubated with HLMs for up to 1 h at two concentrations (100 and 500 μM) and with HepaRG cells for two time periods (8 and 24 h) at one concentration (20 μM). In vitro obtained results were subsequently applied to a 2F‐DCK‐related fatality case. In vitro ‐produced metabolites were investigated using high‐resolution accurate mass spectrometry using Orbitrap mass analyzer technology. Thirteen metabolites were in vitro produced and several metabolic pathways can be postulated. Seven additional metabolites were found in post‐mortem samples (bile and urine) of the case, comprising three Phase II metabolites, which appear to be minor in vivo metabolites. HLMs and HepaRG cell models appear to be complementary and obtained data allowed the identification of several specific 2F‐DCK metabolites in biological samples. In practical terms, observed metabolic ratios suggested that nor‐2F‐DCK (208.1137  m/z ) and a hydrogenated metabolite (224.1443  m/z ) could be proposed as reliable metabolites to be recorded in HRMS libraries in order to improve detection of 2F‐DCK use. Abstract : Molecular network approach (1) allows 2F‐DCK metabolic profile proposal with evaluation using authentic post‐mortem samples and (2) suggests not ‐2F‐DCK and dihydro‐nor‐FDCK metabolites as robust, specific, and sensitive biomarkers of 2F‐DCK use.